2017
DOI: 10.1158/1078-0432.ccr-16-1784
|View full text |Cite
|
Sign up to set email alerts
|

Selective Targeting of Myeloid-Derived Suppressor Cells in Cancer Patients Using DS-8273a, an Agonistic TRAIL-R2 Antibody

Abstract: Purpose Myeloid-derived suppressor cells (MDSC) one of the major contributors to immune suppression in cancer. We recently have demonstrated in preclinical study that MDSC are sensitive to TRAIL receptor 2 (TRAIL-R2) agonist. The goal of this study was to clinically test the hypothesis that targeting TRAIL-R2 can selectively eliminate MDSC. Experimental Design The TRAIL-R2 agonistic antibody (DS-8273a) has been tested in 16 patients with advanced cancers enrolled in a phase 1 trial. The antibody (24 mg/kg) w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
118
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(122 citation statements)
references
References 32 publications
3
118
0
1
Order By: Relevance
“…Our study was focused on the analysis of DR networks in AML cells carrying FLT3‐ITD mutation. This type of analysis has a high clinical relevance, in particular, in view of recent reports that activation of TRAIL‐R2 may downregulate the myeloid‐derived suppressor cells in vivo . These findings increase the interest in the analysis of the DR network in AML cells, in particular focusing on specific mutations, as was done in our study.…”
Section: Discussionsupporting
confidence: 61%
“…Our study was focused on the analysis of DR networks in AML cells carrying FLT3‐ITD mutation. This type of analysis has a high clinical relevance, in particular, in view of recent reports that activation of TRAIL‐R2 may downregulate the myeloid‐derived suppressor cells in vivo . These findings increase the interest in the analysis of the DR network in AML cells, in particular focusing on specific mutations, as was done in our study.…”
Section: Discussionsupporting
confidence: 61%
“…In another study, PMN‐MDSCs were demonstrated to have a shorter lifespan than normal neutrophils and this associated with Trail‐R2 receptor signaling . Importantly, targeting this receptor via an agonistic antibody approach resulted in relatively specific MDSC depletion in both tumor bearing animals and cancer patients …”
Section: Neutrophil Populations In Inflammatory Settingsmentioning
confidence: 99%
“…92 Importantly, targeting this receptor via an agonistic antibody approach resulted in relatively specific MDSC depletion in both tumor bearing animals and cancer patients. 92,93 A separate PMN-MDSC subset has also been characterized during endotoxemia challenge in humans. Pillay et al 10 demonstrated that following LPS stimulation a distinct mature neutrophil population that displays hypersegmented nuclear structure and CD16 hi CD62L lo expression can mediate T cell immunosuppression via ROS and an integrin Mac-1 dependent mechanism.…”
Section: Myeloid-derived Suppressor Cellsmentioning
confidence: 99%
“…Numerous monoclonal antibody (mAb)-based therapies have shown promising efficacy as cancer therapeutics through the direct targeting of tumor antigens or tolerogenic molecules on immune cells (5,6). Although several mAb-based approaches have been developed to directly target exhausted or immunosuppressed T-cells in cancer patients, there are limited mAb-based therapies that could effectively inhibit MDSCs (7). …”
Section: Introductionmentioning
confidence: 99%